The Dynamic of Semantic Loss in Indonesian’s Translation of Al-Qur’an - Moh. Mukhlas (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
The Dynamic of Semantic Loss in Indonesian’s Translation of Al-Qur’an Moh. MukhlasIAIN Ponorogomukhlas.1967@gmail.com AbstractThe phenomenon of semantic loss in the Qur'an, either in the form of expansion of meaning, narrowing of meaning or total change is interesting to be studied, because it will have implications for social and religious life. This study aims to explain the forms and factors underlying the occurrence of semantic loss in the Indonesian translation of the Qur'an. To explore these objectives, the qualitative research was used with a library study approach, where data was collected in a documentary with an interactive analysis model adopted from Miles and Huberman. This study concludes that semantic loss contains in the translation of the Qur'an is in the form of expansion of meaning, narrowing of meaning, total change of meaning, and amelioration, that is the process of changing meaning where the new meaning is perceived to be higher or better than the old meaning. The factors underlying the occurrence of semantic loss are linguistic and non-linguistic factors. Linguistics factors include phonetic aspects, morphological aspects, and syntax, while non-linguistics factors include historical factors, socio-cultural factors that analyze culture based on world views in the socio-cultural context of the perpetrators of language, psychological factors of speakers and speech partners, factors of scientific and technological development.Keywords: semantic loss, amelioration, linguistics, non-linguisticsديناميكية الفقدان الدلالي فى ترجمة القرآن بإندوينسيامحمد مخلاصالجامعة الإسلامية الحكومية بفونوروكو mukhlas.1967@gmail.com الملخصإن ظاهرة الفقدان الدلالي في القرآن، سواء في شكل توسع في المعنى أو تضييق المعنى أو التغيير الكامل، أمر مثير للدراسة، لأنه سيكون له آثار على الحياة الاجتماعية والدينية. تهدف هذه الدراسة إلى شرح الأشكال والعوامل الكامنة وراء حدوث الخسارة الدلالية في الترجمة الإندونيسية للقرآن. لاستكشاف هذه الأهداف ، تم استخدام البحث النوعي مع نهج دراسة المكتبة ، حيث تم جمع البيانات في فيلم وثائقي مع نموذج تحليل تفاعلي اعتمد من مايلز وهوبرمان. تخلص هذه الدراسة إلى أن الفقد الدلالي في ترجمة القرآن في شكل توسع في المعنى ، وتضييق المعنى ، والتغيير الكامل للمعنى ، وتحسينه ، وهذه هي عملية تغيير المعنى حيث يُنظر إلى المعنى الجديد على أن تكون أعلى أو أفضل من المعنى القديم. العوامل الكامنة وراء حدوث الفقد الدلالي هي عوامل لغوية وغير لغوية. تشمل عوامل اللغويات الجوانب الصوتية ، والجوانب المورفولوجية ، وبناء الجملة ، في حين أن العوامل غير اللغوية تشمل العوامل التاريخية ، والعوامل الاجتماعية الثقافية التي تحلل الثقافة على أساس وجهات النظر العالمية في السياق الاجتماعي والثقافي لمرتكبي اللغة ، والعوامل النفسية للمتحدثين والكلام شركاء ، عوامل التطور العلمي والتكنولوجي.الكلمات الرئيسية: الخسارة الدلالية، التحسين، اللسانيات، اللا لسانيات